2021
DOI: 10.3390/ani11051460
|View full text |Cite
|
Sign up to set email alerts
|

Deathly Silent: Exploring the Global Lack of Data Relating to Stranded Cetacean Euthanasia

Abstract: The compromised state of stranded cetaceans means that euthanasia is often required. However, current knowledge and implementation of euthanasia methods remain highly variable, with limited data on the practicalities and welfare impacts of procedures. This study evaluated the available published data on cetacean euthanasia, highlighting knowledge gaps and providing direction to improve stranded cetacean welfare. A total of 2147 peer-reviewed articles describing marine mammal euthanasia were examined. Of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…Notably, the initial shot placement observed appears misaligned with the euthanasia guidance in the New Zealand SOP which states that shots should be a “handspan behind the blowhole” (Boren, 2012; Boys et al, 2022d). Skull morphology among cetacean species is highly variable (Galatius et al, 2020; Gol'din, 2014) and thus species‐specific reference points are required for accurate projectile placement (Boys et al, 2021). However, the cranial morphology of pygmy killer whales, including the anatomical location of the blowhole, is similar to that of pilot whales detailed in the generic New Zealand SOP, meaning that species differences are unlikely to explain melon penetration on this occasion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Notably, the initial shot placement observed appears misaligned with the euthanasia guidance in the New Zealand SOP which states that shots should be a “handspan behind the blowhole” (Boren, 2012; Boys et al, 2022d). Skull morphology among cetacean species is highly variable (Galatius et al, 2020; Gol'din, 2014) and thus species‐specific reference points are required for accurate projectile placement (Boys et al, 2021). However, the cranial morphology of pygmy killer whales, including the anatomical location of the blowhole, is similar to that of pilot whales detailed in the generic New Zealand SOP, meaning that species differences are unlikely to explain melon penetration on this occasion.…”
Section: Discussionmentioning
confidence: 99%
“…While these are recommended in the New Zealand SOP (Boren, 2012; Boys et al, 2022d), soft point projectiles are understood to have reduced penetration ability and lower killing efficiency (Hampton et al, 2014; Knox et al, 2018; Øen & Knudsen, 2007). Indeed, international recommendations suggest the use of only solid projectiles for cetaceans (Boys et al, 2021; Duignan & Anthony, 2000; Hampton et al, 2014; Øen & Knudsen, 2007). The implications of using soft projectiles at this event are unknown since postmortem examination of the cranium was not possible.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, a recent study has shown that immersion with tricaine methanesulfonate (MS-222) is not always efficacious, and a secondary method such as pithing is now recommended [3]. Although additional research is continually being conducted to determine the most appropriate methods for euthanizing non-domestic species, there is still a paucity of information as to what methods work, what does not work, and where improvements can be made to provide the best care for these patients [4,5].…”
Section: Introductionmentioning
confidence: 99%